2015
DOI: 10.1111/jgh.12694
|View full text |Cite
|
Sign up to set email alerts
|

Association between specific mucosa‐associated microbiota in Crohn's disease at the time of resection and subsequent disease recurrence: A pilot study

Abstract: In Crohn's disease, the mucosa-associated microbiota diversity is reduced at the time of surgery, but also differs between patients with different clinical outcomes at 6 months. These findings may provide prognostic information at the time of surgery, allowing identification of patients at increased risk of recurrence, and provide basis for a more targeted approach for therapeutic interventions after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(114 citation statements)
references
References 47 publications
6
107
0
1
Order By: Relevance
“…Notably, the presence of mucosal bacteria associated with saccharolytic metabolism, including Bacteroides, Prevotella, and Parabacteroides species, has been correlated with increased remission compared with the presence of bacteria associated with fermentation and lactic acid production, such as Enterococcus and Veillonella. 77 These studies demonstrate the importance of the global gut microbiota composition and function in the development and severity of IBD.…”
Section: Global Shifts In the Gut Microbiota And Ibdmentioning
confidence: 79%
“…Notably, the presence of mucosal bacteria associated with saccharolytic metabolism, including Bacteroides, Prevotella, and Parabacteroides species, has been correlated with increased remission compared with the presence of bacteria associated with fermentation and lactic acid production, such as Enterococcus and Veillonella. 77 These studies demonstrate the importance of the global gut microbiota composition and function in the development and severity of IBD.…”
Section: Global Shifts In the Gut Microbiota And Ibdmentioning
confidence: 79%
“…Our data in mice showed that high-fibre diet increased Bacteroidetes and decreased Firmicutes, which parallels findings in humans 38 . No-fibre diet enriched Proteobacteria, which has been associated with Western diets and disease states 38,40,41 . On the family level, high-fibre diet supported the outgrowth of Bacteroidaceae, as reported elsewhere 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Microbial patterns in patients with recurrent disease have been demonstrated to have reduced abundance of Firmicutes, in particular, F. prausnitzii (Sokol et al, 2008), as well as increased adherent invasive E. coli (AIEC) (Lepage et al, 2009;Darfeuille-Michaud et al, 2004). In a study exploring changes in the microbiota profile of 12 patients with CD at the time of surgical intervention, biodiversity was lower at the time of surgery and The role of bacteria in Crohn disease was increased 6 months after surgery (De Cruz et al, 2015). However, at 6 months following surgery, biodiversity still remained different in healthy subjects (De Cruz et al, 2015).…”
Section: Dysbiosis and Disease Relapsementioning
confidence: 99%
“…In a study exploring changes in the microbiota profile of 12 patients with CD at the time of surgical intervention, biodiversity was lower at the time of surgery and The role of bacteria in Crohn disease was increased 6 months after surgery (De Cruz et al, 2015). However, at 6 months following surgery, biodiversity still remained different in healthy subjects (De Cruz et al, 2015). This study also found that patients with recurrent disease had a predominance of Enterococcus, whereas those who maintained remission showed predominance of butyrate-producing Firmicutes (De Cruz et al, 2015).…”
Section: Dysbiosis and Disease Relapsementioning
confidence: 99%